Campos divergentes y convergentes de la obesidad y la salud mental - Raquel del Socorro Guillén Riebeling (Psic-Obesidad, 2026)
Obesity and mental health are two complex fields that intersect across biological, psychological, and sociocultural dimensions. The evidence points to a bidirectional relationship between the two conditions. On the one hand, mood disorders may contribute to compensatory eating behaviors, social isolation, and a sedentary lifestyle; on the other hand, obesity can lead to stigma, social rejection, limitations in daily activities, and workplace difficulties, thereby increasing stress and the risk of psychological disorders. It is also believed that certain endocrine and metabolic diseases may be associated with mental health symptoms and disorders, while some pharmacological treatments may contribute to weight gain. Body image is another important mediating factor, due to its influence on self-esteem and emotional well-being. Therefore, timely identification and differential diagnosis are essential. Multidisciplinary care and multimodal interventions allow for a comprehensive approach to physical, psychological, and social factors, thereby strengthening prevention and health promotion.